To determine which equation has no solution, we can analyze each option:
-
3x + 4 = 3x + 3
- Subtracting \(3x\) from both sides gives \(4 = 3\), which is false. This equation has no solution.
-
3x + 4 = 4
- Subtracting \(3x\) from both sides gives \(4 = 4 - 3x\). This simplifies to \(3x = 0\), giving the solution \(x = 0\).
-
3x + 4 = 4x + 3
- Rearranging gives \(3x - 4x = 3 - 4\), or \(-x = -1\), leading to the solution \(x = 1\).
-
3x + 4 = 3x + 3
- This is the same as the first equation and has no solution because it simplifies to \(4 = 3\).
Therefore, the equation with no solution is 3x + 4 = 3x + 3.